Transcriptome‐wide analysis of circRNA and RBP profiles and their molecular relevance for GBM - Julia Latowska‐Łysiak; Żaneta Zarębska; Marcin P. Sajek; Adriana Grabowska; Alessia Buratin; Paweł Głodowicz; Julia O. Misiorek; Konrad Kuczyński; Stefania Bortoluzzi; Marek Żywicki; Jan G. Kosiński; Agnieszka Rybak‐Wolf; et al. (Molecular Oncology)
Glioblastoma (GBM) is the most aggressive and lethal type of glioma, characterized by aberrant expression of noncoding RNAs including circular RNAs (circRNAs). CircRNAs may impact cellular processes by interacting with other molecules—like RNA‐binding proteins (RBPs). The diagnostic value of circRNA and circRNA/RBP complexes is still largely unknown. To explore circRNA and RBP transcript expression in GBM, we performed and further analyzed RNA‐seq data from GBM patients' primary and recurrent tumor samples. We identified circRNAs differentially expressed in primary tumors, the circRNA progression markers in recurrent GBM samples, and the expression profile of RBP genes. Furthermore, we demonstrated the clinical potential of circRNAs and RBPs in GBM and proposed them as stratification markers in de novo assembled tumor subtypes. Additionally, we experimentally validated the subcellular localization of select circRNAs and their interactions with FUS. Subsequently, we showed that circARID1A may play a role in promoting GBM cell proliferation. Overall, we described circRNA‐RBP interactions that could play a regulatory role in gliomagenesis and GBM progression and provided a list of molecular players in GBM for further extensive studies.